Non-local effect on quality factor of micro-mechanical resonator under the purview of three-phase-lag thermoelasticity with memory-dependent derivative - Tiwari R.; Kumar R. (My University, 2025)
Thermoelastic damping is defined as a significant intrinsic dissipative mechanism which represents the loss of energy of micro-/nano-mechanical resonators. It remarkably affects the quality performance of the resonators. It is a very strenuous task to fabricate a resonator of good quality type so that its thermoelastic damping should be minimum. Recently, extensive attention is being paid to fabricate micro-/nano-resonators due to their numerous applications in micro- and nano-electro-mechanical systems. Present study enlightens a new mathematical model with non-local effect as well as memory effect which exhibits the lower values of thermoelastic damping and attenuation compared to the previous existing models without non-local and memory effect. Governing equations are developed in context of three-phase-lag generalized thermoelasticity in the frame of non-local and memory effect. Analytical expressions of significant factors of micro-beam resonator such as thermoelastic damping, attenuation as well as frequency shift are evaluated. Quantitative results are derived to display the influence of effective parameters such as non-local thermal parameter of heat conduction, kernel functions as well as time delay on the variations of thermoelastic damping, attenuation as well as frequency shift. Also, the size effect of micro-beam resonator is being presented on the variations of thermoelastic damping of micro-beam resonator. By discussing the computational results, utility of the present model is being proved. It is believed that the predicted results must be advantageous to design the micro-/nano-mechanical resonators of better quality. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.